Unexpected Behavior of the Heaviest Halogen Astatine in the Nucleophilic Substitution of Aryliodonium Salts. Issue 35 (11th July 2016) - Guérard, François; Lee, Yong‐Sok; Baidoo, Kwamena; Gestin, Jean‐François; Brechbiel, Martin W.
Abstract: Invited for the cover of this issue is the group of François Guérard at the University of Nantes, in collaboration with scientists at the National Institutes of Health in Bethesda. The image depicts the finish of a race between all the halogens, with astatine far ahead of the others. The diaryliodonium at the finish line highlights the unexpectedly high reactivity of astatide towards this class of compounds. Read the full text of the article at10.1002/chem.201600922 . Abstract : " Astatine is definitely a halogen apart ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 12332 ff. (DOI:10.1002/chem.201600922 ).